Anti-aging and antioxidant of four traditional Malaysian plants using simplex centroid mixture design approach - Ranneh, Yazan; Abu Bakar, Mohd Fadzelly; Ismail, Nur Amalina; Kormin, Faridah; Mohamed, Maryati; Md Akim, Abdah; Isha, Azizul (Elsevier, 2021)
Aging is a naturally biological process with adverse effects. The continuous accumulation of reactive oxygen species (ROS) trigger cellular and tissue damage by activating several aging enzymes. The antioxidant properties of traditional medicinal plants used by Jakun aborigine’s community are a promising approach to alleviate aging process and prevent Alzheimer. The aim of the current investigation was to optimize a novel anti-aging formulation from traditional plants (Cnestis palala stem, Urceola micrantha stem, Marantodes pumilum stem and Microporus xanthopus fruiting bodies) using simplex centroid mixture design (SCMD). After selecting the optimal formulations based on desirability function of antioxidant activity (DPPḢ, ABTṠ+ and FRAP), they were further examined against the activity of aging-related-enzymes (collagenase, tyrosinase, acetyl- and butyrylcholinesterase). The single extracts of C. palala, U. micrantha and the binary mixture of C. palala and U. micrantha were the optimal formulations with high antioxidant activities. Single extract of U. micrantha showed the highest inhibition towards matrix metalloproteinase-1 (49.44 ± 4.11 %), while C. palala water extract showed highest inhibitions towards tyrosinase (14.06 ± 0.31%), acetylcholinesterase (32.92 ± 2.13%) and butyrylcholinesterase (34.89 ± 2.84%) enzymes. The single extracts of C. palala and U. micrantha displayed better activity as compared to the binary mixture formulation. In conclusion, these findings could be a baseline for further exploration of novel anti-aging agents from natural resources.